Who is Valued and What is of Value? - Hallett, Graham (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
The subject of values is complex; this short paper will consider the values held by teachers, and who is valued within teaching. The first area to be examined will be the way in which values are expressed in the mechanisms that drive the assessment of classroom practice in Initial Teacher Education. Inevitably, such an examination cannot avoid engaging with a debate around attainment and achievement, through a consideration of what we value in teachers both as professionals and in the way that they meet the learning needs of the children and young people with whom they come into contact in their daily work. This leads to a second area, focussing on the degree to which these values are instrumental in producing and supporting a differentially weighted schooling system, where some pupils are valued more than others.